2014
DOI: 10.1186/1471-2229-14-179
|View full text |Cite
|
Sign up to set email alerts
|

BeMADS1 is a key to delivery MADSs into nucleus in reproductive tissues-De novo characterization of Bambusa edulis transcriptome and study of MADS genes in bamboo floral development

Abstract: BackgroundThe bamboo Bambusa edulis has a long juvenile phase in situ, but can be induced to flower during in vitro tissue culture, providing a readily available source of material for studies on reproductive biology and flowering. In this report, in vitro-derived reproductive and vegetative materials of B. edulis were harvested and used to generate transcriptome databases by use of two sequencing platforms: Illumina and 454. Combination of the two datasets resulted in high transcriptome quality and increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 75 publications
(116 reference statements)
2
37
0
Order By: Relevance
“…The gene structures and amino acid sequences were highly similar to rice MADS homologs (77–92%). Most importantly, all of the predicted proteins contain M, I, K, and C domains, definitive of type II MADS (Shih et al, 2014). When the whole genome of moso bamboo was published (Peng et al, 2013), 34 MADS genes were identified (Peng et al, 2013; Cheng et al, 2017).…”
Section: Applications Of Bamboo In Vitro Flowering—cloning Of Flower-mentioning
confidence: 99%
See 3 more Smart Citations
“…The gene structures and amino acid sequences were highly similar to rice MADS homologs (77–92%). Most importantly, all of the predicted proteins contain M, I, K, and C domains, definitive of type II MADS (Shih et al, 2014). When the whole genome of moso bamboo was published (Peng et al, 2013), 34 MADS genes were identified (Peng et al, 2013; Cheng et al, 2017).…”
Section: Applications Of Bamboo In Vitro Flowering—cloning Of Flower-mentioning
confidence: 99%
“…Five genes did not have the M domain (PheMADS56-4, PheMADS21, PheMADS14, PheMADS29, and PheMADS90; Cheng et al, 2017), while others were very short and contained only the M domain (PheMADS1, PheMADS5, PheMADS64, PheMADS65; Cheng et al, 2017). Thus far it is unknown whether these differences are due to the starting materials (DNA from in vivo flowers in Cheng et al, 2017 vs. RNA from in vitro flowers in Shih et al, 2014). …”
Section: Applications Of Bamboo In Vitro Flowering—cloning Of Flower-mentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison, the molecular aspects of bamboo flowering remain at a nascent stage. Studies have been conducted to characterize a limited number of flowering genes in different bamboo species such as MADS18 from Dendrocalamus latiflorus (Bo et al, 2005), FLOWERING LOCUS T (FT) from P. meyeri (Hisamoto et al, 2008), TERMINAL FLOWER 1 (TFL1) like gene from Bambusa oldhamii (Zeng et al, 2015), FRIGIDA (FRI) from P. violascens (Liu et al, 2015), MADS1 and MADS2 from P. praecox (Lin et al, 2009), 10 genes related to floral transition and meristem identity in D. latiflorus (Wang et al, 2014) and 16 MADS box genes from B. edulis (Shih et al, 2014). Such targeted approaches are being complemented by high-throughput approaches, namely, de novo transcriptome sequencing and suppression subtractive hybridization (Lin et al, 2010; Liu et al, 2012; Zhang et al, 2012; Peng et al, 2013; Gao et al, 2014; Ge et al, 2016; Wysocki et al, 2016; Zhao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%